India's rise: On feet of clay? - Christian Wagner (Stiftung Wissenschaft und Politik (SWP), 2022)
India has risen internationally since the 1990s. The most important reasons for this success are its economic reforms since 1991 and new international constellations since the East-West conflict. Both have earned the country a significantly greater say on global issues, but India's rise is quite fragile due to a range of structural deficits at the national level. Despite economic successes India is in many areas one of the G20's poorest performers. India's rise is in Germany's and Europe's interest. The world's largest democracy is considered to be a partner in shared values and fellow campaigner for a rules-based international order and as a promising market. In addition, India, Germany and Europe increasingly share geopolitical interests. India is seen as a mainstay of future German Indo-Pacific policy. A number of domestic developments in India adversely affect the foundations of cooperation. Since 2014 a decline of democratic procedures and institutions has been apparent and the new economic policy of self-reliance proclaimed in 2020 is based more on partial protectionism than on further integration into the world market. That is why, to manage expectations realistically, German and European policy should be geared more towards common interests than to values.
Keywords: 320; Entwicklung; Wirtschaftslage; Wirtschaftspolitik; Außenpolitik; Internationale Sicherheit; Internationale Beziehungen; Internationale Wirtschaftsbeziehungen; Indien